Preferable in vitro condition for maintaining faithful DNA methylation imprinting in mouse embryonic stem cells. (22nd January 2018) - Lee, Jiyoung; Matsuzawa, Ayumi; Shiura, Hirosuke; Sutani, Akito; Ishino, Fumitoshi
Abstract : Epigenetic properties of cultured embryonic stem cells (ESCs), including DNA methylation imprinting, are important because they affect the developmental potential. Here, we tested a variety of culture media, including knockout serum replacement (KSR) and fetal bovine serum (FBS) with or without inhibitors of Gsk3β and Mek1/2 (2i) at various time points. In addition to the previously known passage‐dependent global changes, unexpected dynamic DNA methylation changes occurred in both maternal and paternal differentially methylated regions: under the widely used condition of KSR with 2i, a highly hypomethylated state occurred at early passages (P1–7) as well as P10, but DNA methylation increased over further passages in most conditions, except under KSR with 2i at P25. Dramatic DNA demethylation under KSR+2i until P25 was associated with upregulated Tet1 and Parp1, and their related genes, whereas 2i regulated the expressions of DNA methyltransferase‐related genes for the change in DNA methylation during the cumulative number of passages. Although DNA methylation imprinting is more labile under KSR with and without 2i, it can be more faithfully maintained under condition of cooperative FBS and 2i. Thus, our study will provide the useful information for improved epigenetic control of ESCs and iPSCs in applications in regenerative medicine. Abstract : The imprinted memory in ESCs and even in ICM cells derived from a BJ hybrid is labile and able to change under variable culture conditions and is mostly sensitive to the presence of 2i or KSR. DNA methylation imprinting can be more faithfully maintained under condition of cooperative FBS and 2i.